Sheath blight resistance in rice (Oryza sativa): A comprehensive review - GHOSH, SAHASRANTIKA; V K, SATYA; C, GOPALAKRISHNAN; P, JEYAPRAKASH; S, VARANAVASIYAPPAN; BASHYAL, BISHNU MAYA; GHOSH, AMAL (The Indian Journal of Agricultural Sciences, 2025)
The growing global population and the rising trend of rice consumption are expected to drive up future rice (Oryza sativa L.) demand. If India, China, and Indonesia's recent pattern of rising per capita consumption of rice continues, the overall increase in rice consumption might possibly outpace the population rise. The reduction of cultivable area and the yearly crop loss valued at billions of dollars as a result of sheath blight disease and changing climate aggravate the issue. The pathogen's extremely wide host range, great genetic variability, and the lack of any discernible natural resistance in the existing rice germplasm make it difficult to control. It is imperative to discover countermeasures against the disease in order to minimize the threat to global food security and reduce losses in rice yield. In this review, details on the sheath blight symptoms, pathogen character, disease cycle, host range, QTLs, genome wide association study (GWAS), genomic selection approach, key genes related to sheath blight resistance are summarized.